Abundance of white lace lerp psyllids on understorey and canopy river red gums and relationships with foliar sugars and tannins. (20th July 2022) - Steinbauer, Martin James; Tanha, Reza
Abstract: 1. Trees present herbivorous insects with the greatest diversity of resources of any plant growth form. Both ontogeny and shading can alter suitability for arboreal insect herbivores. 2. We conducted a longitudinal study of tagged 'mature' (>12 months old) Eucalyptus camaldulensis leaves to compare the suitability of understorey and canopy trees for the leaf senescence‐inducing psyllid, Cardiaspina albitextura . We quantified sugars and tannins as possible predictors of nymphal abundance. 3. Canopy leaves hosted double the number of nymphs as understorey leaves. Variation among individual trees (understorey and canopy) was the most important source of heterogeneity explaining psyllid abundance, although relative leaf age significantly influenced oviposition on canopy leaves. The diversity of foliar sugars was higher among canopy leaves than among understorey leaves. There was significant between‐tree diversity in total hydrolysable tannins (HTs) and total condensed tannins (CTs) among understorey trees but not among canopy trees. Heterogeneity among understorey and canopy trees was explained by greater diversity of ellagitannins (HTs) than of CTs. 4. Shading is detrimental to the survival of nymphs on both host types, but sugars are unlikely to explain variation in suitability. Vescalagin (an ellagitannin) was negatively correlated with the abundance of nymphs on both host types. Abstract : Travel tower (15 m) used to photograph tagged leaves hosting nymphs of Cardiaspina albitextura in canopies of river red gums at Fotheringham Reserve, Dandenong, Australia.